Effectiveness of tune mass damper in the reduction of the seismic response of the structure - Rakicevic, Z.T. and Bogdanovic, A. and Jurukovski, D. and Nawrotzki, P. (My University, 2012)
A shaking table testing of a 16.6 t five storey steel frame structure with and tuned mass damper (TMD) named as Tuned Mass Control System (TMCS) installed at the top has been carried out in the Dynamic Testing Laboratory at the Institute of Earthquake Engineering and Engineering Seismology (IZIIS) in Skopje, Republic of Macedonia. For estimation of the effectiveness of Tuned Mass Control System (TMCS) large number of shaking table experiments have been performed. Simulating different earthquake time histories on the model structure with and without TMCS it has been demonstrated that this system is capable to reduce the responses in order from 10% to more than 50% depending on the frequency content of the seismic input and the corresponding sensitivity of the structure. Given a high quality analytical model of a structure and a dynamic absorber, a series of variant analyses have been performed within the study to investigate the effect of the individual parameters and evaluate the efficiency of the dynamic absorber. The analyses have been performed to define the effect of the location of the absorber, also, upon the dynamic behaviour of the structure in the case the absorber is installed at the different level (storey) of the structure. Comparative analysis of the structure with TMCS having optimally tuned its mechanical properties versus structure that has TMCS having the same mechanical properties as tested specimen showed that the TMCS additionally improves the structural behaviour, depending on frequency content of earthquake excitation.
Keywords: Tuned mass damper; Shaking table testing; Analytical modelling; Optimization; Effectiveness